Changes in Resting and Exercise Hemodynamics Early After Heart Transplantation: A Simulation Perspective - Haberbusch, Max; De Luca, Daniela; Moscato, Francesco (Frontiers in Physiology, 2020)
Introduction: During heart transplantation (HTx), cardiac denervation is inevitable, thus typically resulting in chronic resting tachycardia and chronotropic incompetence with possible consequences in patient quality of life and clinical outcomes. To this date, knowledge of hemodynamic changes early after HTx is still incomplete. This study aims at providing a model-based description of the complex hemodynamic changes at rest and during exercise in HTx recipients (HTxR). Materials and Methods: A numerical model of early HTxR is developed, that integrates intrinsic and autonomic heart rate (HR) control into a lumped-parameter cardiovascular system model. Intrinsic HR control is realized by a single-cell sinoatrial node model. Autonomic HR control is governed by aortic baroreflex and pulmonary stretch reflex and modulates sinoatrial node activity through neurotransmitter release. The model is tuned based on published clinical data of 15 studies. Simulations of rest and exercise are performed to study hemodynamic changes associated with HTxR. Results: Simulations of HTxR at rest predict a substantially increased HR (93.8 vs 69.5 bpm) due to vagal denervation while maintaining normal cardiac output (5.2 vs 5.6 L/min) through a reduction in stroke volume (55.4 vs 82 mL). Simulations of exercise predict markedly reduced peak cardiac output (13 vs 19.8 L/min) primarily resulting from diminished peak HRs (133.9 vs 169 bpm) and reduced ventricular contractility. Yet, the model results show that HTxR can maintain normal cardiac output for low-to-medium exercise intensity by increased stroke volume augmentation through the Frank-Starling mechanism. Conclusions: Relevant hemodynamic changes occur after HTx. Simulations suggest that (1) increased resting HRs solely result from the absence of vagal tone; (2) chronotropic incompetence is the main limiting factor of exercise capacity whereby peripheral factors play a secondary role; and (3) despite the diminished exercise capacity, HTxR can compensate chronotropic incompetence by a preload-mediated increase in stroke volume augmentation, and, thus maintain normal cardiac output in low-to medium-intensity exercise.